Investigating the connection between safety culture, affective commitment, and organizational performance in manufacturing industry / Muhammad Zulhilmi Ibrahim, Nur Ashikin Johari and Nurul Hidayana Mohd Noor - Ibrahim, Muhammad Zulhilmi; Johari, Nur Ashikin; Mohd Noor, Nurul Hidayana (Universiti Teknologi MARA, Perlis, 2025)
The manufacturing industry is known as one of the most hazardous industries, which not only requires occupational solid laws and regulations but also demands the commitment of all employees. Shared commitment and value on safety are essential factors in developing an organizational strategy, leading to economic effectiveness and resource utilization. The study is designed to determine the role of affective commitment as a mediator in affecting the correlation between safety culture and organizational performance. Data (n = 200) was gathered from employees of Honda Manufacturing Malacca. The research model is analyzed using the Structural Equation Modeling (SEM) method. The results discovered that safety culture and affective commitment significantly influence organizational performance. Besides, affective commitment partially intermediates safety culture and organizational performance relationships. This result implies that a psychological construction has implications for individual decisions to continue their membership, adhere to safety procedures, and perform their duties for the organization.